Who backs up credence claims?: Roles for government as a competent authority in assuring quality attributes - Noonan, John; Batt, Peter; Warren, J (International Society of Horticultural Science, 2011)
The role of government and intergovernmental mechanisms to assure food safety is well established. However, government also has a role in establishing and verifying a range of acceptable production approaches and consequential outcomes relating to credence attributes. The role of government in providing baseline information on the supply side and competent inspection services to verify the effectiveness of control measures at the production and processing levels of the value chain is identified. A meta-accreditation process, whereby government endorses various food safety and quality certification schemes that are coupled with credence attribute assurances is the most cost effective mechanism for government to pursue.